Health Worker Attitudes toward Rural Service in Liberia : Results from Qualitative Research - Attah, Ramlatu; Lievens, Tomas; Vujicic, Marko; Brown-Annan, Julie (World Bank, Washington, DC, 2013)
In Liberia, the maldistribution of health workers is particularly pronounced as 14 years of civil war exacerbated the concentration of experienced health workers in urban areas. The government has identified this challenge as a priority area for policy intervention. The objective of this study was to explore the drivers of health workforce choice including job location. It presents the results from preparatory qualitative research that fed into the design of a discrete choice experiment (DCE). The qualitative study interviewed 26 registered nurses, midwives, and physician assistants about their current working conditions, their job location preference, and priority areas for change in working conditions. Content analysis was used to analyze the data. The study shed light on health worker job preferences and their working conditions, and identified six job attributes that health workers consider to be important when choosing a job. These were pay, transport, availability of medical materials and infrastructure, housing, workload, and further training opportunities. These attributes were chosen because they reflect the frequency to which they were cited during the interviews and the extent to which they were amenable to policy intervention. Associated attribute levels were chosen for each attribute to reflect current work conditions and the levels of change that will be necessary to trigger changes in job choice. The relative weight of each of these attributes in location choice has been quantitatively determined through the follow-up DCE. Although the main aim of this study was to feed into the DCE design, it incidentally throws light on a wider variety of issues with regard to health worker career choice, motivation, and performance.